Pengembangan E-Modul Fisika Materi Energi dan Perubahannya Berbasis Potensi Lokal Terintegrasi Ayat Al-Qur’an untuk Meningkatkan Keterampilan Berpikir Kritis Siswa SMK - Lusiati Musfiroh; Sri Jumini; Moh. Yusuf Amin Nugroho (Kappa Journal, 2025)
This research aims to develop a physics E-Module of the material "Energy and Its Changes" based on local potential that is integrated with Qur'an verses in order to improve the critical thinking skills of vocational school students. This research uses the Research and Development (R&D) method with the ADDIE development model consisting of Analyze, Design, Develop, Implement, and Evaluate stages. Data was obtained through observation, interviews, questionnaires, documentation, as well as pretest and posttest tests. Validation is carried out by media and material experts, while practicality is assessed by students, and effectiveness is analyzed through the Wilcoxon Signed-Rank Test and N-Gain calculation. The results of the study showed that the E-Modules developed had a very high level of validity with an average validation score of 93%. The practicality of the E-Module is also considered very practical with an average score of 88.7%. The use of E-Modules has been proven to be effective in improving students' critical thinking skills, as evidenced by the Wilcoxon test which shows that H₁ is accepted, as well as an N-Gain value of 0.603 which is in the medium category. This e-Module successfully integrates physics material with local contexts and religious values, and provides a contextual, independent, and meaningful learning experience for students. Thus, this E-Module is suitable for use as a physics learning medium at vocational schools.